Effect of dietary bamboo charcoal powder supplementation on carcass quality of spent laying hen - Sabangbarn, Chanudee; Boonyoo, Adisorn; Danglao, Boonnumpa; Wiangtham, Chiradon (Journal of Vocational Education in Agriculture, 2024)
Effect of dietary bamboo charcoal powder (BCP) supplementation on carcass quality of spent laying hen (Rhode Island Red ×Single Comb White Leghorn). The objective was to study the production potential and carcass quality of spent laying hen. The study were investigated in 18, 104 weeks of age chicks. The chicks were randomly assigned to 3 experimental groups (Completely randomized design; CRD), 6 replicates of 1 chicks each. Group 1, the chicks were fed control diet without BCP (0%). Group 2 and 3 the chicks were fed the diet containing BCP at 0.25 and 0.50 percent, respectively. The carcass quality and meat quality were observed and when the chickens were 111 weeks of age at the end of the experiment. The results showed that the BCP was not effect on carcass quality. Therefore, the BCP can use in spent laying hen diet up to 0.50% without the effect on carcass quality.